The effectiveness, cost-effectiveness, budget impact, and return on investment of scaling up tuberculosis screening and preventive treatment in Brazil, Georgia, Kenya, and South Africa: a modelling study - Vesga, Juan F, PhD; Mohamed, Mona Salaheldin, PhD; Shandal, Monica, MSc; Jabbour, Elias, MSc; Lomtadze, Nino, MD; Kubjane, Mmamapudi, PhD; Trajman, Anete, Prof; Meyer-Rath, Gesine, Prof; Avaliani, Zaza, PhD; Rotich, Wesley, MSc; Mwai, Daniel, PhD; Croda, Julio, MD; et al. (The Lancet global health, 2025)
SummaryBackgroundClosing the tuberculosis diagnostic gap and scaling up tuberculosis preventive treatment (TPT) are two global priorities to end tuberculosis. We aimed to estimate the cost-effectiveness, budget impact, and societal return on investment of a comprehensive intervention to improve tuberculosis screening and prevention in Brazil, Georgia, Kenya, and South Africa—four distinct epidemiological settings. MethodsIn this modelling study, in partnership with national tuberculosis programmes we defined a set of interventions (the intervention package) related to tuberculosis screening and TPT in three priority populations: people with HIV, household contacts, and a country-defined high-risk population (people deprived of liberty [Brazil], people accessing care for injection drug use [Georgia], people in informal settlements in nine districts with a high prevalence of tuberculosis [Kenya], and people in the 22 subdistricts with the highest prevalence of tuberculosis [South Africa]). We developed transmission models calibrated to country-specific epidemiology and collated cost data for tuberculosis-related activities and patient costs in 2023 US dollars (US$). We compared the intervention package scaled up to reach all priority populations by 2030 to a status quo scenario based on projected tuberculosis epidemiology over a 27-year time horizon (Jan 1, 2024, to Dec 31, 2050); to delineate the impact of intervention components, we also evaluated the intervention package without TPT. Outcomes were health system and societal costs, number of tuberculosis episodes, tuberculosis deaths, and disability-adjusted life years (DALYs). We calculated the budget impact, health system cost per DALY averted, and societal return on the health system investment for each country. Outcomes were discounted at 3% per annum. FindingsWith the status quo scenario, by 2050, tuberculosis incidence is projected to be 41 per 100 000 population (95% uncertainty range 32–53) in Brazil, 45 per 100 000 population (36–60) in Georgia, 214 per 100 000 population (146–266) in Kenya, and 261 per 100 000 population (133–406) in South Africa. The percentage of all tuberculosis episodes prevented by implementing the intervention package in all priority populations is projected to be 15·0% (12·8–17·5) in Brazil, 14·3% (13·1–15·8) in Georgia, 21·3% (15·2–27·6) in Kenya, and 26·4% (21·1–31·8) in South Africa by 2050. If implemented without TPT (ie, tuberculosis disease screening alone), corresponding reductions were lower at 10·4% (8·6–12·2) in Brazil, 10·2% (9·5–11·2) in Georgia, 12·6% (9·5–15·9) in Kenya, and 16·8% (13·0–20·4) in South Africa. In 2030, the percentage of the national tuberculosis programme budget required for the intervention package was 62% in Brazil, 10% in Georgia, 67% in Kenya, and 44% South Africa. The incremental cost per DALY averted of the intervention package compared with the status quo in all priority populations is $386 in Brazil, $491 in Georgia, $53 in Kenya, and $160 in South Africa. The corresponding societal return per health system dollar invested is projected to be $51 in Brazil, $8 in Georgia, $27 in Kenya, and $54 in South Africa. InterpretationScaling up tuberculosis screening and TPT requires substantial investment but is projected to be cost-effective compared with the status quo, to greatly reduce tuberculosis incidence, and to provide large returns on investment. FundingWorld Health Organization.